A novel fullerene-like B30N30 structure: Stability and electronic property. (June 2016) - Yin, Deqiang; Yang, Yang; Yang, Yi; Fang, Hui
Abstract: Boron Nitride (BN) and carbon (C) are chemical analogues of each other and share similar structures mainly from one dimensional (1D) nanotube (NT), two-dimensional (2D) nanosheet (NS), to three dimensional (3D) diamond structures. Moreover, because of the difference in electronegativity, B and N form strongly polarized covalent bonds and exhibit unusual mechanical and thermal properties. Under inspiration from the fullerene-C60 structures, we proposed a B30 N30 -fullerene like structure, and studied its thermodynamical and vibrational stability with first principles calculations. The cohesive energy and vibrational analysis confirmed its stability. Furthermore, the electronic properties showed that the proposed structure may occupy the more activity due to the anisotropic distributions of charge density. The stability of BN-fullerene should stimulate experimental efforts to establish whether above finding has a realistic experimental counterpart.